Cyberbullying Analysis in Behaviorism Psychology Perspective - Roby, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the phenomenon of Cyberbullying through the perspective of behavioral psychology, focusing on how bullying behavior is formed and maintained in cyberspace. A qualitative approach with descriptive analytical methods was used in this study to explore the influence of reinforcement and punishment in influencing the behavior of perpetrators and victims. Data were collected through literature studies, in-depth interviews with victims and perpetrators, and analysis of social media content involving bullying behavior. The results of the study indicate that Cyberbullying behavior is often acquired through the process of observation and imitation, as explained in the social learning theory by Albert Bandura. Cyberbullying perpetrators tend to imitate aggressive behavior that they observe in cyberspace, especially those involving public figures or famous people. In addition, positive and negative reinforcement received by the perpetrator, such as social attention or avoidance of negative feelings, play an important role in strengthening the behavior. The psychological impact of Cyberbullying is very significant for victims, who can experience stress, anxiety, depression, and decreased self-esteem. On the other hand, perpetrators may feel strengthened by social responses, but may experience a decrease in their ability to control themselves. This study suggests the importance of digital literacy education, strict monitoring of online behavior, and the implementation of stricter penalties on digital platforms as an effort to reduce the prevalence of Cyberbullying and create a safer online environment.